The Role of Health Insurance in Facilitating Access to Healthcare Utilization: A Case Study of BPJS Kesehatan Users in Banten Province - Hadi Kurniawanto; Muhammad Angga Anggriawan; Billy Tejaarief; Kenedi (Postgraduate, University of Mataram, 2025)
Access to healthcare remains a major challenge, especially in developing countries, due to limited infrastructure, medical personnel, and funding. In 2017, the World Bank and WHO reported that nearly half of the world's population struggled to access healthcare due to high costs, including in Indonesia. This study examines the factors influencing BPJS Kesehatan participation and its impact on healthcare utilization. Using probit models and regression techniques, the analysis highlights key determinants, including residence, age, marital status, healthcare utilization, sanitation, household size, income, agricultural participation, health conditions, and employment status. The study also evaluates the effect of insurance coverage on healthcare visits using Negative Binomial Regression and IV Poisson GMM methods. Results indicate that while insurance increases healthcare utilization, factors such as geographic location and out-of-pocket expenses influence access. Findings suggest the need for targeted policies to improve insurance accessibility, particularly in rural areas, and address economic barriers. Limitations include the cross-sectional nature of the data and potential biases in self-reported information. Future research should explore longitudinal data and additional variables to better understand health insurance dynamics.